Female same-sex couples act long-term financially rational? (Sociologisk Forskning, 2017)
One of the challenges faced by research on the gendered transition to parenthood is how to dismantle the interconnected nature of biology, gender and economic reasoning. We contribute to this aim by comparing division of parental leave in different-sex couples (DSC) and female same-sex couples (SSC). Motherhood identity formation appears to be strong in DSC as well as SSC. Net of this, gender is an important predictor of parental leave in DSC. To some extent, SSC seem to divide the leave in a more long-term financially rational way than DSC do.